RESENSI BUKU: MEMBUKA PIKIRAN MENUJU KETERPADUAN - Hanifah, Nurdinah (Mimbar Sekolah Dasar, 2014)
This book entitled The Integrated Thematic Learning exists to provide an alternative source of reference in the figure of thematic learning The book consists of nine chapters presenting the textbook material unloading ranging from the study of theory up to how the application of thematic learning integrated concerning government regulations on integrated thematic learning curriculum is described thoroughly in 2013 by graduates of the Graduate University of Indonesia.Keywords: integrated, thematic, learning.